Fungus-initiated catalytic reactions at hyphal-mineral interfaces drive iron redox cycling and biomineralization. (1st September 2019) - Yu, Guang-Hui; Chi, Zhi-Lai; Teng, H. Henry; Dong, Hai-Liang; Kappler, Andreas; Gillings, Michael R.; Polizzotto, Matthew L.; Liu, Cong-Qiang; Zhu, Yong-Guan
Abstract: The ability of fungi to weather a wide range of minerals influences plant nutrition and enhances global biogeochemical cycles of life-essential elements. The fungus-mineral interface plays a key role in weathering, but the specific mechanisms underlying these processes remain poorly understood. Here, we examined fungal-mineral weathering using hematite and Trichoderma guizhouense. We showed that hematite dissolution increased over cultivation time, with the formation of secondary minerals up to ∼3000 µm −2 at the interfaces after 66 h cultivation. Of the hematite associated with hyphae, approximately 15% was converted to the secondary mineral ferrihydrite. Importantly, superoxide radicals were detected at the hyphal tips and along the whole hyphae. During cultivation, a high concentration (∼1000 nM) of hydroxyl radical was also detected. Synchrotron radiation based spectromicroscopies at fungus-mineral interfaces suggest that fungus hyphae alter the local redox state of iron and thus are redox-active. These findings indicate that fungus-initiated catalytic reactions occur at hyphal-mineral interfaces, in view of the fact that superoxide does not diffuse far from the site of formation. Furthermore, these results also suggest that the catalytic reactions may serve as a new strategy for microbial iron uptake. Together, these findings constitute a significant step forward in understanding the ways that fungi make minerals available to biological systems.